KERJASAMA INDONESIA - INDIA DALAM MEMPERKUAT PERDAGANGAN MINYAK KELAPA SAWIT PERIODE 2016 - 2018 - Dyah Sekarini Ramadhanti, (2021)
This study examines the cooperation between Indonesia and India in strengthening the trade of Palm Oil in the period of 2016 - 2018. Palm oil produced by Indonesia has always increased, so this had led to the formation of Indonesian and Indian cooperation in strengthening the trade in Palm Oil. This research raises the research question "How is the Implementation of Cooperation between Indonesian and India in Strengthening the 2016 - 2018 Palm Oil Trade?". To be able to answer these questions the author uses a number of theories and concepts such as Internation Trade Theory, Comperative Advantage Concept, International Cooperation Theory and National Interest Theory. This method uses descriptive qualitative method, which focuses on the use of primary data originating from interview and official documents and other secondary data support the discrussion and understanding of this research. This research was conducted to find out about the condition of Palm Oil in Indonesian, a form of cooperation between Indonesian and Indian in Strengthening.